Healing under pressure: hyperbaric oxygen and myocutaneous flap repair for extreme persistent perineal sinus after proctectomy for inflammatory bowel disease - Chan, XHS; Koh, CE; Glover, M; Bryson, P; Travis, SPL; Mortensen, NJ (Association of Coloproctology of Great Britain and Ireland, 2014)
Aim Persistent perineal sinus (PPS) following proctectomy for inflammatory bowel disease affects about 50% of patients. Up to 33% of cases of PPS remain unhealed at 12 months and the most refractory cases are unhealed at 24 months despite optimal conventional therapy. Reports of hyperbaric oxygen therapy (HBOT) for chronic wounds and Crohn's perianal disease led us to explore perioperative HBOT with rectus abdominis myocutaneous (RAM) flap repair in a highly selected group of patients with extreme PPS who had failed all other interventions. Method Patients with extreme PPS received preoperative HBOT (a 90-min session at 2.2–2.4 atmospheres, five times per week for 5–6 weeks, for a total of up to 30 sessions), before abdominoperineal PPS excision and perineal reconstruction with vertical or transverse RAM flap repair within 2–4 weeks of completing HBOT. Postoperative HBOT (10 further 90-min sessions) was administered within 2 weeks where practicable. Results Between 2007 and 2011, four patients with extreme PPS underwent RAM flap repair with preoperative HBOT; two also received postoperative HBOT. The median (range) duration of PPS before HBOT was 88.5 (23–156) months. All patients had previously failed multiple (5 to > 35) surgical procedures. Complete healing occurred in all patients at a median (range) follow-up of 2.5 (2–3) months. There were no further hospital admissions for PPS at a median (range) follow-up of 35 (8–64) months. Conclusion Hyperbaric oxygen therapy combined with PPS excision and perineal reconstruction with a RAM flap led to complete perineal healing in four patients with extreme PPS and appears a safe and effective extension to the therapeutic pathway for exceptionally treatment-refractory PPS.